Lifting the Iron Curtain: School-age Education and Entrepreneurial Intentions - Oliver Falck; Robert Gold; Stephan Heblich (Center for Economic Studies and ifo Institute (CESifo), 2015)
We exploit Germany's reunification to identify how school-age education affects entrepreneurial intentions. We look at university students in reunified Germany who were born before the Iron Curtain fell. During school age, all students in the West German control group received formal and informal education in a free-market economy, while East German students did or did not receive free-market education. Difference-in-differences estimations show that school-age education in a free-market economy increases entrepreneurial intentions. An event study supports the common-trends assumption. Results remain robust in matched samples and when we exploit within-student variation in occupational intentions to control for unobserved individual characteristics.
Keywords: L26; I21; J24; P30; 330; entrepreneurship; socialism; formal education; informal education